ANALISIS KESALAHAN SISWA KELAS VI SD NEGERI GUNTUR DALAM MENYELESAIKAN SOAL CERITA PADA MATERI VOLUME PRISMA DENGAN MENGGUNAKAN LANGKAH POLYA - Tsamrotul Ihtiari, Dhiya Ayu (STAINU Purworejo, 2018)
This research to determine what errors students experience in solving story problems and their causal factors on prism volume material based on polya’s analysis. This type of research is descriptive research with a quantitative approach. The instruments in this study were test questions and interview guidelines. The subjects in this study were on high-ability student, one medium-capable student and one low ability student. The researcher also triangulated time. Data analysis techniques used in this study consisted of data collection, data reduction, and data presentation, and clonclusion drawing. Based on the results of the analysis, it can be concluded that: (1) the mistakes made by students are not identifying what is known, what information is there and what they are looking for, not writing the formula in full, not writing units of volume and changing them to other units, and not writing conclusions from the calculations that have been done; (2) the factors that cause the error are feeling by writing what is know and being asked will waste time, misinterpret the problem, want to solve the problems, lack of prerequisite abilities in units of length and volume, running out of time, i feel the answer is correct and i’m not used to checking the answer again.